On “Hearing” Voices and “Seeing” Things: Probing Hallucination Predisposition in a Portuguese Nonclinical Sample with the Launay-Slade Hallucination Scale-Revised - Castiajo, Paula; Pinheiro, Ana P. (Frontiers in Psychology, 2017)
The experience of hallucinations is a hallmark of psychotic disorders, but they are also present in other psychiatric and medical conditions, and may be reported in nonclinical individuals. Despite the increased number of studies probing the incidence of nonclinical hallucinations, the underlying phenomenological characteristics are still poorly understood. This study aimed to examine the psychometrics proprieties of the Portuguese adaptation of the 16-item Launay-Slade Hallucinations Scale (LSHS), the phenomenological characteristics of nonclinical hallucinatory experiences in a Portuguese sample, and the relationship between clinical symptoms and hallucination predisposition. Three-hundred-and-fifty-four European Portuguese college students completed the LSHS. Of those, 16 participants with high LSHS scores and 14 with low LSHS scores were further screened for clinical symptoms. A three-factor solution for the LSHS Portuguese version proved to be the most adequate. Intrusive or vivid thoughts and sleep-related hallucinations were the most common. Although fundamentally perceived as positive experiences, all types of hallucinations were described as uncontrollable and dominating. However, the more pleasant they were perceived, the more controllable they were assessed. In addition, hallucination predisposition was associated with increased clinical symptoms. These results corroborate the lower severity of hallucinations in the general population compared to psychotic individuals. Further, they support an association between clinical symptoms and increased vulnerability to hallucinations. Specifically, increased schizotypal tendencies and negative mood (anxiety and depression) may be related to increased psychotic risk.